Can Self-Esteem Protect Against the Deleterious Consequences of Self-Objectification for Mood and Body Satisfaction in Physically Active Female University Students? - Thøgersen-Ntoumani, Cecilie; Ntoumanis, Nikos; Cumming, J.; Bartholomew, K.; Pearce, G. (Human Kinetics, 2011)
Using objectification theory (Fredrickson & Roberts, 1997), this study tested the interaction between self-objectification, appearance evaluation, and self-esteem in predicting body satisfaction and mood states. Participants (N = 93) were physically active female university students. State self-objectification was manipulated by participants wearing tight revealing exercise attire (experimental condition) or baggy exercise clothes (control condition). Significant interactions emerged predicting depression, anger, fatness, and satisfaction with body shape and size. For participants in the self-objectification condition who had low (as opposed to high) appearance evaluation, low self-esteem was associated with high depression, anger, and fatness and low satisfaction with body shape and size. In contrast, for participants with high self-esteem, these mood and body satisfaction states were more favorable irrespective of their levels of appearance evaluation. For female exercisers, self-esteem-enhancing strategies may protect against some of the negative outcomes of self-objectification.